The Refugee Crisis and Right-Wing Populism: Evidence from the Italian Dispersal Policy - Francesco Campo; Sara Giunti; Mariapia Mendola (Institute of Labor Economics (IZA), 2021)
This paper examines how the 2014-2017 'refugee crisis' in Italy affected voting behaviour and the rise of right-wing populism in national Parliamentary elections. We collect unique administrative data throughout the crisis and leverage exogenous variation in refugee resettlement across Italian municipalities induced by the Dispersal Policy. We find a positive and significant effect of the share of asylum seekers on support for radical-right anti-immigration parties. The effect is heterogeneous across municipality characteristics, yet robust to dispersal policy features. We provide causal evidence that the anti-immigration backlash is not rooted in adverse economic effects, while it is triggered by radical-right propaganda.
Keywords: D72; F22; O15; P16; 330; dispersal policy; voting behavior; refugee crisis; immigration; impact evaluation